The "New York City Marathon": participation and performance trends of 1.2M runners during half-century - Vitti, A.; Nikolaidis, P. T.; Villiger, E.; Onywera, V.; Knechtle, B. (Research in Sports Medicine, 2020)
The aim of the present study was to examine trends in participation, performance, age and nationality during a ~ 50-years period in the largest dataset ever studied in the "New York City Marathon". We analysed 1,174,331 finishers (women, n= 349,145, age 39.7 ± 8.7 years; men, n= 825,186, 41.7 ± 9.2 years). The overall participation increased across calendar years for all nationalities, and this increase was more pronounced in women, which resulted in a decreasing men-to-women ratio. Men were faster and older than women. Ethiopians and Kenyans were the fastest and youngest in women and men, respectively. Japanese were the slowest and Germans were the oldest in both sexes. Race time increased across years. Coaches and fitness trainers should be aware of these trends and should emphasize the development of training programs for older and slower runners.